Excitotoxic insult results in a long-lasting activation of CaMKIIα and mitochondrial damage in living hippocampal neurons. - Nikolai Otmakhov (PLoS ONE, 2015)
Over-activation of excitatory NMDA receptors and the resulting Ca2+ overload is the main cause of neuronal toxicity during stroke. CaMKII becomes misregulated during such events. Biochemical studies show either a dramatic loss of CaMKII activity or its persistent autonomous activation after stroke, with both of these processes being implicated in cell toxicity. To complement the biochemical data, we monitored CaMKII activation in living hippocampal neurons in slice cultures using high spatial/temporal resolution two-photon imaging of the CaMKIIα FRET sensor, Camui. CaMKII activation state was estimated by measuring Camui fluorescence lifetime. Short NMDA insult resulted in Camui activation followed by a redistribution of its protein localization: an increase in spines, a decrease in dendritic shafts, and concentration into numerous clusters in the cell soma. Camui activation was either persistent (> 1-3 hours) or transient (~20 min) and, in general, correlated with its protein redistribution. After longer NMDA insult, however, Camui redistribution persisted longer than its activation, suggesting distinct regulation/phases of these processes. Mutational and pharmacological analysis suggested that persistent Camui activation was due to prolonged Ca2+ elevation, with little impact of autonomous states produced by T286 autophosphorylation and/or by C280/M281 oxidation. Cell injury was monitored using expressible mitochondrial marker mito-dsRed. Shortly after Camui activation and clustering, NMDA treatment resulted in mitochondrial swelling, with persistence of the swelling temporarily linked to the persistence of Camui activation. The results suggest that in living neurons excitotoxic insult produces long-lasting Ca2+-dependent active state of CaMKII temporarily linked to cell injury. CaMKII function, however, is to be restricted due to strong clustering. The study provides the first characterization of CaMKII activation dynamics in living neurons during excitotoxic insults.